IMPROVING THE METHODOLOGY OF PREPARING STUDENTS FOR SOCIAL COOPERATION IN HIGHER EDUCATION (Scientific journal of the Fergana State University, 2025)
In recent years, under the influence of new approaches to education, the issue of establishing a technological approach as an essential indicator of improving the activities of educational institutions has been studied. In this context, the designated theory and practice of education emphasize the need to improve the activities of all educational institutions on a common scientific and methodological basis.In some scientific research, the terms "cooperation," "partnership," "coordination," and "joint action" have been used as synonyms. In our opinion, the concept of "cooperation" is broader and implies joint effective activity to achieve common goals. This article discusses the interpretation of the concept of cooperation, the foundations of cooperative pedagogy, the development of university students' skills in social cooperation, and the methodology for preparing students for social cooperation.